Algivorous Cercozoa shape the community composition of cryptogamic covers, the dominant vegetation in Polar Regions - Ana Cristina Martinez Rendon; Christina Braun; Maria T Kappelsberger; Jens Boy; Angelica Casanova-Katny; Karin Glaser; Kenneth Dumack (PANGAEA, 2025)
Soil algae are the most important primary producers where vascular plants are absent, as in the Arctic and Antarctica. They give rise to species-rich microbial food webs in biological soil crusts (biocrusts). The terrestrial snow- and ice-free areas are in permanent expansion as glaciers retreat, leaving behind extensive areas of uncovered rock and new soil. Biocrusts stabilize the soil surface and have an important role in soil development. However, the microbial food webs and the nutrient and energy flow to higher trophic levels remain largely unexplored. Here, we characterized the microbial predator-prey dynamics of polar soils by combining molecular and traditional culturing techniques. Using high-throughput sequencing of environmental samples, we assessed the biodiversity and function of soil protists, applying a trait-based approach for acquiring and describing functional traits, i.e., the feeding behavior of heterotrophic protists in relation to microalgae. The study encompasses the analysis of biocrust samples of three polar regions. In the Arctic, one region was sampled - Svalbard in the Arctic Ocean (78°N) in July 2021. In Antarctica, two regions were studied, i.e. King George Island (62°S) in the South Shetland archipelago of Maritime Antarctica and the Thala Hills oasis in Enderby Land, East Antarctica (67°S), between January and March 2022.